Implematasi Aeschipper Class Untuk Enkripsi URL di Sistem Informasi Akademik Fakultas Teknik Universitas Diponegoro - Subari, Arkhan; Manan, Saiful (Jurnal Sistem Komputer, 2014)
In web programming GET method can use to send data from client to server. Weaknees of the GET method is the appearance of transmitted data or variables in the URL. Users can easily change variables used and when it is executed, variable data will also be executed. It is very vulnerable to attack by malicious users with some techniques such as XSS or SQL injection. These weaknesses can be resolved with use encryption techniques to URLs that use the GET method, such as AES encryption. The process is encrypt variables on client side and decrypt on server side to retrieve actual data. Thus variable is not shown in the URL, so if there will be an attack attempt difficult. Academic Information System (AIS) of Engineering Faculty, as a web-based application also uses several modules that use the GET method for sending data. Thus addition of the security level using the URL encryption is needed to improve security of system and data on the AIS. The result is a variable that is sent with GET method is not display on URL on three modules, namely the main menu page, change the password and a link out of the syste . The encryption process adds time access to system by an average of 0:05 s, so that the outline does not affect system performance . Keywords: web applications, POST and GET, URL, encryption, AES, academic information system.